The Implementation of Interactive Methods in Islamic Religious Education Learning at RA Masjid Al-Azhar, Permata Puri, Semarang - Septiyani Septiyani; Arsan Shanie; Mursid Mursid (Universitas Al-Hikmah Indonesia, 2025)
Islamic Religious Education (IRE) at the Early Childhood Education stage plays an important role in shaping children's religious values and behaviour. The main challenge faced by ECE teachers today is how to present IRE material effectively so that it is easily understood by students. This study aims to analyse the application of interactive learning in improving children's understanding of PAI material at RA Masjid Al-Azhar Permata Puri. The study uses a qualitative approach with a field study method. Data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that interactive learning is applied through group activities, practical activities, and the direct involvement of children in the learning process. The findings also indicate that this strategy is able to increase the enthusiasm, participation, and conceptual understanding of students towards PAI material. Thus, interactive learning is considered relevant and effective in supporting the success of PAI learning in early childhood.